Beyond linguistic terrorism: Hip Hop in Brazil & South Africa as decolonial communication - Alves, Camila Cristina de Oliveira; Williams, Quentin (InterAção, 2026)
This article presents a comparative study on decolonial communication practices in Hip Hop cultures from Sao Paulo (Brazil) and Cape Town (South Africa), examining how artists employ multilingualism to resist colonial linguistic terrorism. Analyzing a composition from Sao Paulo and a bilingual praxis in Cape Town’s Cape Flats, the study investigates strategies of linguistic resistance and cultural citizenship in peripheral urban contexts marked by colonialism and racialization. Grounded in Bakhtinian theory of plurilingualism and Veronelli’s (2016) concept of decolonial communication, this research demonstrates that Hip Hop constitutes a transnational space for circulation of African/Afrodiasporic ideas, where historically marginalized communities transform rigid monolingual spaces into dynamic multilingual places. In Sao Paulo, the incorporation of Brazilian Yoruba and Pretuguês (Black Portuguese) in rap compositions challenges Portuguese linguistic hegemony while recentering Afro-Brazilian cosmologies. In Cape Town, the Heal the Hood project exemplifies how bilingual Kaaps-English performances challenge standard language ideologies inherited from Apartheid, creating pedagogically transformative third spaces in multilingual classrooms. The comparison between both contexts reveals significant convergences in cultural resistance strategies, including use of digital technologies to create living archives of marginalized languages and knowledge, development of culturally sustaining pedagogies, and construction of transatlantic African-Afrodiasporic solidarities. Simultaneously, it illuminates specificities related to language policies and racialization histories in each country: Brazil’s officially monolingual policy contrasts with South Africa’s official multilingualism, yet both contexts exhibit persistent linguistic marginalization. The study contributes to broader understanding of how popular cultures promote epistemic justice and social transformation in Global South urban peripheries.